2018
DOI: 10.32674/jis.v8i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Destination Motivation, Cultural Orientation, and Adaptation: International Students’ Destination-Loyalty Intention

Abstract: This study aims to understand factors predicting destination-loyalty intention in international education. A sample of 378 long-term (n=195) and short-term (n=183) international students participated in the study carried out in 2014 through an on-line survey at the University of Bergen, Norway. Using a series of hierarchical regression analyses, the researchers found that among short-term students, destination motivation (pull), orientation to mainstream and heritage culture together with psychological adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
2
17
0
1
Order By: Relevance
“…Satisfaction as an outcome might also lead to revisiting a particular country or recommending it to other students. Jamaludin, Sam, and Sandal (2018) investigated the issue of destination loyalty, and their results indicated that psychological adaptation of short-term international students was significant in predicting the intention to revisit and recommend the destination to people in their home country. The International Student Barometer, StudyPortals, QS Student Satisfaction, and a number of other assessments measure the level of student satisfaction.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Satisfaction as an outcome might also lead to revisiting a particular country or recommending it to other students. Jamaludin, Sam, and Sandal (2018) investigated the issue of destination loyalty, and their results indicated that psychological adaptation of short-term international students was significant in predicting the intention to revisit and recommend the destination to people in their home country. The International Student Barometer, StudyPortals, QS Student Satisfaction, and a number of other assessments measure the level of student satisfaction.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…International students adapt themselves with the host culture so that they can blend better. The view is supported by Jamaludin and Sam (2018) who stated that international students need time for orientation to the host culture. Further, their research highlights the benefit of sociocultural adaptation for international students that they tend to recommend and to return to the host destination.…”
Section: Appearancementioning
confidence: 99%
“…Literature analysis highlights some important issues. They are the following: international students are considered as an object for understanding the global landscape of higher education [27], the process of integration with university life [28], problems of cross-national communication and relations between international and domestic students [29][30][31][32], questions of creating a friendly, equal university atmosphere with acknowledgement of international students' diversity [33], international students' processes of adaptation [34,35], the role of mentors in these processes and in the process of fostering leadership development outcomes for international students [36,37], issues of academic and social support [38], psychological wellbeing of international students and their psychological, academic and university adjustment [39][40][41][42][43], international students' motivation [44,45] and the impact of education abroad and its importance for international students' future career [46].…”
Section: Introductionmentioning
confidence: 99%